2015
DOI: 10.7727/wimj.2014.230
|View full text |Cite
|
Sign up to set email alerts
|

Ascites in Ovarian Carcinoma – Reliability and Limitations of Cytological Analysis

Abstract: Peritoneal cytology of ascitic fluid is highly specific but has relatively low sensitivity, particularly in the case of endometrioid ovarian carcinoma. In order to increase sensitivity, peritoneal cytology should be combined with monoclonal antibodies and other biochemical and immunohistochemical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In the present study, preoperative ascites regression was independently associated with both improved cytoreduction and OS/PFS, suggesting ascites regression could confer benefits through mechanisms other than optimal cytoreduction. Whether the patient could achieve ascites regression or not could be influenced by many factors, such as histological type, chemotherapy response, tumor volume and sites and even invasion depth . The subgroup patients with higher optimal resection rate and chemotherapy response rate were more likely to show the disappearance of ascites, which could explain the relationship between ascites regression and prognosis to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, preoperative ascites regression was independently associated with both improved cytoreduction and OS/PFS, suggesting ascites regression could confer benefits through mechanisms other than optimal cytoreduction. Whether the patient could achieve ascites regression or not could be influenced by many factors, such as histological type, chemotherapy response, tumor volume and sites and even invasion depth . The subgroup patients with higher optimal resection rate and chemotherapy response rate were more likely to show the disappearance of ascites, which could explain the relationship between ascites regression and prognosis to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Precise cytological diagnosis of pelvic HGSC from ascites is important for tumour staging and therapeutic decision‐making , especially for patients who need accurate tumour typing by preoperative ascites cytology before receiving neoadjuvant chemotherapy. However, based on published studies, the sensitivity of peritoneal cytology ranges from 50%‐70% . Zivadinovic et al showed that the false‐negativity in ascites cytology for ovarian carcinoma was 30.2%, whereas the false‐positivity was 6.38% for all histological types of malignant ovarian tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cytology of ascites is an important for diagnosis, therapeutic decision and prognostic prediction. The results of secondary cytology after treatment are also important independent prognostic indicators that are highly correlated with optimal surgery outcomes, recurrence and overall survival rate . However, an increasing number of studies have shown that the morphological examination of cytological samples is not a highly sensitive diagnostic tool to distinguish metastatic adenocarcinoma from reactive mesothelial cells in ascites.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, it was concluded that peritoneal cytology of ascitic fluid is highly specific (93.61%) but it has a relatively low sensitivity (68.92%). In 30.02%, peritoneal cytology had false-negative results, and in 6.38%, it showed false-positive results [11].…”
Section: Cytology Biochemistry and Immunohistochemistry Of Ascitic mentioning
confidence: 99%